The role of neutrophils in neuro-immune modulation. (January 2020) - Kanashiro, Alexandre; Hiroki, Carlos Hiroji; da Fonseca, Denise Morais; Birbrair, Alexander; Ferreira, Raphael Gomes; Bassi, Gabriel Shimizu; Fonseca, Mirian D.; Kusuda, Ricardo; Cebinelli, Guilherme Cesar Martelossi; da Silva, Katiussia Pinho; Wanderley, Carlos Wagner; Menezes, Gustavo Batista; et al.
Graphical abstract: Highlights: Neutrophils are an immunological and diffuse source of neurotransmitters. Neutrophils regulate sensory neuron functions and vice-versa. Neutrophils play a crucial role in inflammatory disorders in the central nervous system. Abstract: Neutrophils are peripheral immune cells that represent the first recruited innate immune defense against infections and tissue injury. However, these cells can also induce overzealous responses and cause tissue damage. Although the role of neutrophils activating the immune system is well established, only recently their critical implications in neuro-immune interactions are becoming more relevant. Here, we review several aspects of neutrophils in the bidirectional regulation between the nervous and immune systems. First, the role of neutrophils as a diffuse source of acetylcholine and catecholamines is controversial as well as the effects of these neurotransmitters in neutrophil's functions. Second, neutrophils contribute for the activation and sensitization of sensory neurons, and thereby, in events of nociception and pain. In addition, nociceptor activation promotes an axon reflex triggering a local release of neural mediators and provoking neutrophil activation. Third, the recruitment of neutrophils in inflammatory responses in the nervous system suggests these immune cells as innovative targets in the treatment of central infectious, neurological and neurodegenerative disorders. Multidisciplinary studies involving immunologists and neuroscientists are required to define the role of the neurons-neutrophils communication in the pathophysiology of infectious, inflammatory, and neurological disorders.